Preliminary overview and evaluation of a stepped solar distiller with internal reflective walls and borosilicate vacuum tubes - Saettone Olschewski, Erich Arturo (2017)
The present study demonstrates that the current use of stepped solar distillers can be enhanced to increase seawater desalination. To this end, we designed a stepped solar still with internal reflective walls and attached a set of borosilicate vacuum tubes with heat pipes; these heat pipes, in turn, were attached to plates containing seawater inside the distiller. The average global efficiency was calculated in 71.5%; the volume of distilled water per unit area (designated as V'exp) and the volume of distilled water per unit area of distiller and per unit daily solar energy (V¿exp) were also calculated. On a sunny day, with an incident solar energy of 19.93 MJ/m2, V'i was 5690 cm3/m2 and V¿exp was 285.5 cm3/m2 MJ; meanwhile, on a cloudy day, with 12.63 MJ/m2 of energy, V'exp was 3648 cm3/m2 and V¿exp was 288.8 cm3/m2 MJ. Since V¿exp varies only slightly under different weather conditions, we propose that it should be used to compare the performance of stepped solar stills that do and do not contain vacuum tubes. Thus, it was proved that the still containing the vacuum tubes had a global efficiency and V¿exp that were 32.4% greater than those without vacuum tubes.